2017
DOI: 10.1007/s40806-017-0112-x
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind: Towards an Evolutionary Theory

Abstract: Theory of mind is an important mental faculty. However, despite almost half a century of research, we only have a limited understanding of its evolutionary past. The present article proposes a novel hypothesis on the origin of this unique human capacity. According to this hypothesis theory of mind descended from two, closely related, defensive reactions, namely tonic immobility and immobilization stress. Both reactions are conserved in many vertebrate species and are highly prevalent in immature individuals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 331 publications
(389 reference statements)
0
8
0
Order By: Relevance
“…Indeed, interindividual synchronicity of strange-face illusions was described in dyads (Caputo, 2013). From an evolutionary perspective, Tsoukalas (2018) proposed that eye-to-eye contact could be the precursor of theory-of-mind in humans through the evolution of tonic immobility and immobilization stress. In fact, during eye-to-eye gazing, postural immobilization is a compelling behavior that can be easily observed in participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, interindividual synchronicity of strange-face illusions was described in dyads (Caputo, 2013). From an evolutionary perspective, Tsoukalas (2018) proposed that eye-to-eye contact could be the precursor of theory-of-mind in humans through the evolution of tonic immobility and immobilization stress. In fact, during eye-to-eye gazing, postural immobilization is a compelling behavior that can be easily observed in participants.…”
Section: Discussionmentioning
confidence: 99%
“…The two-camera system would also provide control for smiling, laughing, and other face and body movements. Preliminary trials by experienced observers showed that strange-face illusions are greatly increased in strength and duration with respect to naive observers [as predicted by the postural immobilization hypothesis (Tsoukalas, 2018), while perceptual hypotheses (e.g. Troxler effect) are…”
Section: Limitations Of the Researchmentioning
confidence: 96%
“…Other approaches posit that fictions are adaptive because they would train or enhance our social skills (Zunshine, 2006;Mar and Oatley, 2008). However, human social cognitive capacities, such as Theory of Mind (Gerrans, 2002;Tsoukalas, 2018), and human behavioral preferences, such as morality (Sperber and Baumard, 2012;Baumard et al, 2013;Tomasello, 2015), have been selected by natural selection and do not need fiction consumption to fully develop. If it was adaptive for individuals to be more cooperative, more cooperative individuals, that is individuals genetically more motivated to cooperate, would be naturally selected without the need to go through the implementation of the cognitive capacities needed for the behaviors of producing fictions.…”
Section: State Of the Current Hypothesesmentioning
confidence: 99%
“…The opposite of theory of mind is uniformity of mind where others have same beliefs and desires as our own. However, despite almost half a century of research, its evolutionary origin is largely unknown [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cooking with fire forced the early Homo species to live, cook, and eat together, encouraging close large social gathering and interaction. The brain of Homo erectus was doubled to 1100 cm3 by the increase in body size, the environmental adaptation to the open habitat of all different climates, and the social adaptation to the close large social gathering. The period between 800,000 and 200,000 years ago is the period of the strongest climate fluctuation worldwide.…”
mentioning
confidence: 99%